Sphingolipids as Modulators of SARS-CoV-2 Infection - Törnquist, Kid; Asghar, Muhammad Yasir; Srinivasan, Vignesh; Korhonen, Laura; Lindholm, Dan (Frontiers in Cell and Developmental Biology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the COVID-19 pandemic with severe consequences for afflicted individuals and the society as a whole. The biology and infectivity of the virus has been intensively studied in order to gain a better understanding of the molecular basis of virus-host cell interactions during infection. It is known that SARS-CoV-2 binds to angiotensin-converting enzyme 2 (ACE2) via its spike protein. Priming of the virus by specific proteases leads to viral entry via endocytosis and to the subsequent steps in the life cycle of SARS-CoV-2. Sphingosine and ceramide belong to the sphingolipid family and are abundantly present in cell membranes. These lipids were recently shown to interfere with the uptake of virus particles of SARS-CoV-2 into epithelial cell lines and primary human nasal cells in culture. The mechanisms of action were partly different, as sphingosine blocked, whilst ceramide facilitated viral entry. Acid sphingomyelinase (ASM) is vital for the generation of ceramide and functional inhibition of ASM by drugs like amitriptyline reduced SARS-CoV-2 entry into the epithelial cells. Recent data indicates that serum level of sphingosine-1-phosphate (S1P) is a prognostic factor for COVID2 severity. Further, stimulation of sphingosine-1-phosphate receptor 1 (S1PR1) might also constrain the hyper-inflammatory conditions linked to SARS-CoV-2. Here, we review recent exciting findings regarding sphingolipids in the uptake of SARS-CoV-2 and in the course of COVID-19 disease. More studies are required on the mechanisms of action and the potential use of antidepressant drugs and sphingolipid modifiers in SARS-CoV-2 infections and in the treatment of the more serious and fatal consequences of the disease.